2014
DOI: 10.1111/jace.13262
|View full text |Cite
|
Sign up to set email alerts
|

Stability and CMAS Resistance of Ytterbium‐Silicate/Hafnate EBCs/TBC for SiC Composites

Abstract: Multilayer ytterbium-hafnate/silicate coatings deposited by directed vapor deposition and designed to protect SiC-based ceramic matrix composites were assessed to determine their thermochemical stability and resistance to attack by molten silicate deposits (CMAS). The study revealed that reactions occurring at the interface between Yb 2 Si 2 O 7 and Yb 4 Hf 3 O 12 layers promote coating delamination following isothermal annealing for 100 h/1500°C while coating architectures involving Yb 2 SiO 5 in contact with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
88
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 26 publications
4
88
0
Order By: Relevance
“…Within the surface reaction layer faceted apatite and globular fluorite grains, all of order 1 m, are embedded into much larger garnet grains suggesting that the garnet grows more slowly, engulfing the finer grains. To confirm this hypothesis, previously suggested for both Yb-and Y-based coatings, 13 Fig. 5(a) and (b), are comparable to the size of the apatite and fluorite grains.…”
Section: Cmas Interaction With Ybzo and Ybhosupporting
confidence: 75%
See 4 more Smart Citations
“…Within the surface reaction layer faceted apatite and globular fluorite grains, all of order 1 m, are embedded into much larger garnet grains suggesting that the garnet grows more slowly, engulfing the finer grains. To confirm this hypothesis, previously suggested for both Yb-and Y-based coatings, 13 Fig. 5(a) and (b), are comparable to the size of the apatite and fluorite grains.…”
Section: Cmas Interaction With Ybzo and Ybhosupporting
confidence: 75%
“…Based on comparison of the penetration depth they concluded that both YZO and YbZO are more resistant to infiltration than GdZO, suggesting that coatings using the smaller RE cations might offer better performance. 16 Results by the current authors, meanwhile, showed that YbO 1.5 -based coatings are only moderately resistant to CMAS infiltration at 1300 • C. 13 In this case it was hypothesized that the ineffective CMAS mitigation observed with YbHO is related to a high Yb concentration in the re-precipitated fluorite and the apparently sluggish crystallization of a garnet silicate in addition to apatite. Testing the same YbHO coatings at 1500 • C resulted primarily in the growth of an aluminosilicate in the cuspidine family rather than apatite.…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations